2002
DOI: 10.1177/000992280204100706
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Eating Patterns and Symptoms of Pica in Children and Adolescents with Sickle Cell Disease

Abstract: Summary: The objective of this study was to examine the incidence and relationship of pica symptoms and dysfunctional eating patterns in children and adolescents with sickle cell disease (SCD). Children and caregivers (n = 146) completed questionnaires assessing eating difficulties and symptoms of pica. Information also was collected from medical records and analyzed for relationships with dysfunctional eating patterns. Incidence of problems and their association with disease parameters of SCD were examined. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Ivascu et al 2 published a retrospective review of 480 patients with SCD that reported a pica prevalence ranging from 14.8% to 23.3% in the age group of 10–19 years. Lemanek et al 3 have reported a significant association between disease severity (increased frequency of care‐giver and child reported pain episodes) with care‐giver ratings of dysfunctional eating patterns. Dysfunctional eating patterns may represent a coping mechanism to the stress associated with chronic and recurrent pain.…”
Section: Discussionmentioning
confidence: 99%
“…Ivascu et al 2 published a retrospective review of 480 patients with SCD that reported a pica prevalence ranging from 14.8% to 23.3% in the age group of 10–19 years. Lemanek et al 3 have reported a significant association between disease severity (increased frequency of care‐giver and child reported pain episodes) with care‐giver ratings of dysfunctional eating patterns. Dysfunctional eating patterns may represent a coping mechanism to the stress associated with chronic and recurrent pain.…”
Section: Discussionmentioning
confidence: 99%
“…8 BEZOAR Children with SCD have an increased incidence of pica, the mouthing or eating of nonfood items. 9 The incidence of pica decreases with age, but it is as high as 50% in preschoolaged children with SCD. 9 Although rare, gastric or intestinal bezoars resulting from ingestion of hair or foam can be lifethreatening.…”
Section: Hepatic Sequestrationmentioning
confidence: 99%
“…9 The incidence of pica decreases with age, but it is as high as 50% in preschoolaged children with SCD. 9 Although rare, gastric or intestinal bezoars resulting from ingestion of hair or foam can be lifethreatening. [10][11][12] While taking the history of a child with SCD and abdominal pain, one must remember to ask about eating nonfood items.…”
Section: Hepatic Sequestrationmentioning
confidence: 99%
“…Although one fourth of SCD children are affected by pica, it has not gained the focus of health care providers. Searching for biological explanations makes the clinician focus on aspects unrelated to psychological stressors [ 67 ].…”
Section: Introductionmentioning
confidence: 99%